A cross-country analysis of the determinants of insurance supply and demand - Khairudin Damhoeri, (Penerbit Universiti Kebangsaan Malaysia, 1993)
Past studies in international insurance have not adequately addressed the importance of the relationship between the forces of supply and demand and assumed away any relationship between life and non-life insurance towards gaining a better understanding of this still under-researched area, a two-insurance market model is developed. In the empirical estimation of the model, the technique of three stage least square is employed. The empirical findings suggest that life and non-life insurance are complements. both in the demand and supply sides. A number of variables from the broad c1asses of economic, sociopolitical and regulatory variables were found to be significant in determining insurance supply and demand. Of specific variables different than those found in previous studies, the lack of civil liberty was found to negatively affect non-life insurance demand while a mandatory reinsurance cession requirement negatively affects non-life insurance supply